2020
DOI: 10.1016/j.healun.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular T-cell‒mediated rejection in transbronchial and mucosal lung transplant biopsies is associated with future risk of graft loss

Abstract: BACKGROUND: We previously developed molecular assessment systems for lung transplant transbronchial biopsies (TBBs) with high surfactant and bronchial mucosal biopsies, identifying Tcell-mediated rejection (TCMR) on the basis of the expression of rejection-associated transcripts, but the relationship of rejection to graft loss is unknown. This study aimed to develop molecular assessments for TBBs and mucosal biopsies and to establish the impact of molecular TCMR on graft survival. METHODS: We used microarrays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“… 36 It is possible that misclassification between diagnostic cohorts could have influenced results of our analyses. Future studies incorporating outcome measures may shed additional light on the relationship of dd-cfDNA, AR and graft injury, and histopathology, not to mention more speculative markers such as intragraft gene expression profile signatures 37 and epigenetic signatures such as DNA methylation. 38 Nevertheless, our study design and sample size permits insights regarding dd-cfDNA fractions and performance of a clinical assay across diverse types of LT allograft injury and health.…”
Section: Discussionmentioning
confidence: 99%
“… 36 It is possible that misclassification between diagnostic cohorts could have influenced results of our analyses. Future studies incorporating outcome measures may shed additional light on the relationship of dd-cfDNA, AR and graft injury, and histopathology, not to mention more speculative markers such as intragraft gene expression profile signatures 37 and epigenetic signatures such as DNA methylation. 38 Nevertheless, our study design and sample size permits insights regarding dd-cfDNA fractions and performance of a clinical assay across diverse types of LT allograft injury and health.…”
Section: Discussionmentioning
confidence: 99%
“…[126][127][128] A recent study showed that microarray analysis of rejection-associated transcripts from single-piece transbronchial biopsies is correlated with rejection histology. 129,130 It is still unclear whether these ancillary techniques can improve the diagnostic accuracy of standard histology in LTx but results are promising.…”
Section: Ancillary Techniques To Improve Diagnostic Utility Of Biopsies In Acute Cellular Rejectionmentioning
confidence: 99%
“…One example includes the presence of acute fibrinous and organizing pneumonia on late (>3 months after the transplantation) transbronchial biopsies, which occurred in 6% of transplant patients, and which proved to be a strong risk factor for CLAD, specifically RAS ]. Molecular gene expression signatures previously applied in other solid organ transplants could also be of considerable interest as a specific T-cell signature could be identified in transbronchial and endobronchial biopsies, which was associated with graft loss [32]. Other relevant rejection signatures could also be identified including a normal, antibody-mediated rejection and injury signature of which the prognostic importance is still unknown [33].…”
Section: Biopsy Signaturesmentioning
confidence: 99%